Microanatomical Studies on Pineal Gland of Adult Ram - Gopi Krishna, B. (Indian Journal of Veterinary Anatomy, 2018)
The pineal gland in adult ram was highly vascularised and showed a very thin capsule. Capsule was made up ofÂ collagen and reticular fibres with indistinct lobulation. The parenchyma consisted of pinealocytes and interstitial cells. The neuroglial cells were categorised into three types viz., Type-1 cells were large, oval (or) round with one (or) two processesÂ and distributed as small groups. The Type-2 cells had large, elongated (or) oval nuclei whereas Type-3 cells were smaller and showed numerous fine processes mainly associated with blood vessels. PAS reaction was mild in the capsule, strong inÂ pinealocytes and intense in blood vessels of the pineal gland. The pinealocytes and the interstitial cells showed an intense reaction for acid phosphatase and very mild reaction for alkaline phosphatase.